PERAN DINAS SOSIAL SOSIAL DALAM REHABILITASI ORANG DENGAN GANGGUAN JIWA (ODGJ) DI JOMBANG - Rahmawati, Diana (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
This study aims to determine 1. How is the role of the social service in handling ODGJ in Jombang Regency. 2. Obstacles experienced by the Social Service in handling ODGJ in Jombang Regency. 3. Effectiveness of ODGJ Rehabilitation at the Social Service of Jombang Regency. This type of research is qualitative, this type of research does not use calculation procedures or numbers and does not use measuring instruments. This qualitative method only describes an event or events. Sources of data used are primary and secondary sources. The results showed that the role of the Social Service in handling ODGJ patients was quite good. In addition, the Social Service has carried out its role in handling ODGJ sufferers in Jombang Regency, namely providing skills guidance, physical guidance, and spiritual guidance. Constraints faced in handling ODGJ are due to lack of human resources, inadequate infrastructure, low community participation, lack of budget, this is the obstacle why until now the handling of the Rehabilitation of People with Mental Disorders (ODGJ) is still not fully effective. the Ministry of Social Affairs is also experiencing problems due to lack of funds.Keywords: Role, Rehabilitation, ODGJ AbstraksiPenelitian ini bertujuan untuk mengetahui 1. Bagaimana peran dinas sosial dalam penanganan ODGJ di Kabupaten Jombang. 2. Kendala yang dialami oleh Dinas Sosial dalam penanganan ODGJ di Kabupaten Jombang. 3. Efektivitas Rehabilitasi ODGJ pada Dinas Sosial Kabupaten Jombang. Jenis penelitian ini bersifat kualitatif yang jenis penelitiannya tidak menggunakan prosedur perhitungan atau angka-angka dan tidak menggunakan alat ukur, Metode kualitatif ini hanya memaparkan suatu peristiwa atau kejadian. Sumber data yang digunakan adalah sumber primer dan juga sumber sekunder. Hasil penelitian menunjukkan bahwa Peran Dinas Sosial dalam penanganan penderita ODGJ sudah cukup baik, Selain itu Dinas Sosial telah menjalankan perannya dalam penanganan Penyandang ODGJ di Kabupaten Jombang yaitu memberikan bimbingan keterampilan, bimbingan fisik, dan bimbingan kerohanian. Kendala yang dihadapi dalam penanganan ODGJ ini karena masih Kekurangan sumber daya manusia, Sarana prasarana yang kurang memadai, Rendahnya Partisipasi masyarakat, Minimnya Anggaran, hal inilah yang menjadi hambatan mengapa sampai saat ini penanganan Rehabilitasi Orang Dengan Gangguan Jiwa (ODGJ) masih belum efektif sepenuhnya, Dinas Sosial juga mengalami hambatan karena kurangnya dana. Kata Kunci: Peran, Rehabilitasi, ODGJ.